A hospital based study to access the usefulness of using the combination regime of the ferric carboxy maltose, vitamin B12 and folic acid as a treatment of severe anemia among pregnant women in a rural tribal community of South Gujarat - Vayeda Maitri; Desai Tushar; Modi Dhiren; Desai Shrey; Desai Gayatri (Wolters Kluwer Medknow Publications, 2022)
Introduction: Anemia is most common morbidity in pregnancy and micronutrient deficiency is its most common cause in India. Objective: It is to assess the beneficiary effects as well as side effects of single parenteral administration of ferric carboxymaltose (FCM), Vitamin B12, and folic acid as treatment of severe anemia during pregnancy. Methods: This pre-post intervention study was done from April 2018 to March 2019 at a charitable hospital. 100 pregnant women were treated with one infusion of FCM (1000 mg), along with intramuscular Vitamin B12 (500 mcg) and folic acid (15 mg) followed by daily oral supplementation of iron (100 mg) up to delivery. Results: Compared to baseline, absolute increase in hemoglobin was 2.9 g/dl (P < 0.001) and 5.4 g/dl (P < 0.001) after 6 weeks of infusion and at delivery, respectively. 63.9% of women turned nonanemic and none had severe anemia at delivery. No serious side effect was reported and none needed blood transfusion at any time during the study. Conclusion: FCM along with Vitamin B12 and folic acid might be considered for treating severe anemia in pregnancy in resource-poor settings.